My dad, he's one of a kind - Soubakeavathi, Rethinasamy (The Star, 2022)
The saying goes ’Behind every independent woman, is an open-minded father who trusted her and not society’ – my father is a picture-perfect example of this. My Father, Mr. Rethinasamy Muniandy is 80 years old. If I were to share about my Father-honestly, I wouldn't know where to start nor where to end. Perhaps I should start with my Mom. While my Mom was rather orthodox about how a daughter should be brought up, it is my Father who made sure that I was treated equally with my three elder brothers and not left out in any way.